Neuraxial Anesthesia in Parturients with Low Platelet Counts. (July 2016) - Bernstein, Jeffrey; Hua, Betty; Kahana, Madelyn; Shaparin, Naum; Yu, Simon; Davila-Velazquez, Juan
Abstract : The obstetric anesthesiologist must consider the risk of spinal–epidural hematoma in patients with thrombocytopenia when choosing to provide neuraxial anesthesia. There are little data exploring this complication in the parturient. In this single-center retrospective study of 20, 244 obstetric patients, the incidence of peripartum thrombocytopenia (platelet count <100, 000/mm 3 ) was 1.8% (368 patients). Of these patients, 69% (256) received neuraxial anesthesia. No neuraxial hematoma occurred in any of our patients. The upper 95% confidence limit for spinal–epidural hematoma in patients who received neuraxial anesthesia with a platelet count of <100, 000/mm 3 was 1.2%. Abstract : Published ahead of print May 6, 2016